Analisis Perilaku Sosial Masyarakat Terhadap Pandemi Menggunakan Metode Fuzzy C-Means - Mirhan Siregar; Murhaban (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
The COVID-19 pandemic has significantly altered social behavior worldwide, including in Indonesia. To understand society's response to the pandemic, this study employs the Fuzzy C-Means (FCM) method to cluster social behavior based on three main criteria: adherence to health protocols, attitudes toward vaccination, and access to information. Data were collected from 67 respondents through an online questionnaire and analyzed using a fuzzy-based clustering approach that allows each respondent to have membership degrees in more than one cluster. The study identified three primary clusters. Cluster 1 consists of individuals with high adherence to health protocols and a positive attitude toward vaccination, with access to valid information. Cluster 2 represents individuals with moderate adherence and a neutral attitude toward vaccination, and variable access to information. Cluster 3 comprises individuals with low adherence to health protocols, negative attitudes toward vaccination, and a reliance on unverified information sources. This study reveals that access to valid information plays a significant role in shaping individuals' attitudes toward vaccination and compliance with health protocols. The Fuzzy C-Means method proved effective in identifying diverse social behavior patterns, offering a comprehensive understanding of society's response to the pandemic. The findings of this study are expected to contribute to the formulation of more targeted public policies to address different societal groups